The Last Train Through Harecastle Tunnel - Clarke, Alan; Pullen, Gerry; O'Callaghan, Richard; Brooke, Paul; Reid, Ian (bfi, 2016)
It’s the weekend and Fowler, a young man who is a trainspotter is using the time to take the last train scheduled to pass through Harecastle Tunnel, which is scheduled to close. While on the train, he meets an assortment of people taking the same journey, but not for the same purpose. Some find his hobby as dumb, like his coworkers. Some find his hobby fascinating such as Mrs. Dyson and her husband. Although Fowler originally envisioned his journey to be a one-man trip, it becomes a journey filled with people from all walks of life. Originally broadcast on October 1st 1969 as an episode of "The Wednesday Play", "The Last Train Through Harecastle Tunnel" is drastically different from Clarke's previous television productions with "Half Hour Story", with the length and scale increased. The cast of characters are of a theatrical film's worth, with the main character of Fowler encountering a large number of people throughout - with each of them being slightly offbeat. ... There is much in common with the tone of Wes Anderson films with their strangely off-center characters. Clarke also worked in a differing format for "The Last Train Through Harecastle Tunnel" - on video. Most of the production was shot on PAL video format - the studio norm for many BBC productions at the time (though minor exterior shots were shot on film). Visually the format may look different but the qualities and techniques of his previous television productions with extreme close-ups and low angle shots being there, but as it was shot on video cameras which didn't have the freeing movements available with film cameras, shots are quite still for the most part - something that would change with his following production for "The Wednesday Play". [dvdcompare.net]
Keywords: DVD-Video